The Entrepreneurial State: Debunking Public vs Private Sector Myths (an excerpt) - MAZZUCATO, Mariana (Journal of Economic Sociology, 2021)
In the book The Entrepreneurial State, Mariana Mazzucato challenges the widespread idea that the State cannot pick winners, that it is clumsy, bureaucratic and incapable of entrepreneurial risk taking. Her analysis is not just Keynesian; it is also Schumpeterian. The role of the State is not limited to interventions in the macroeconomy as a “market fixer” or as the passive financer of public R & D. The State is also seen as entrepreneur, risk taker and market creator. Mazzucato’s argument goes well beyond the role played by government in countries that have recently forged ahead (Japan in the 1980s or South Korea in the 1990s) to focus on the role played by the public sector agencies of the United States, the wealthiest country in the world and an active promoter of “free markets,” in making risky investments behind the Internet and in funding most of the crucial elements behind the “stars” of the information revolution, companies such as Google and Apple. The Journal of Economic Sociology publishes Chapter 1 of the book, “From Crisis Ideology to the Division of Innovative Labour,” in which the State is presented as an entrepreneurial agent, one taking on the most risky and uncertain investments in the economy. The State does not “derisk” as if it has a “magic wand” that makes risks disappear. It takes on risks, shaping and creating new markets. The author displays the role the State has played in the past, in areas like Silicon Valley, and the role that it can play in the future in areas like the “green revolution.”